Impact of Mindfulness-Based Cognitive Therapy on Depression, Anger and Emotion Regulation of Veterans' Spouses - S.A. Mehri Nejad; L. Ramezan Saatchi (Afarand Scholarly Publishing Institute, 2016)
Aims: Having spent many years in mutual life with the vetrans with physical and mental disorders, the spouses of the veterans are facing with mental problems. Therefore, it is necessary to find a way to help the spouses, to improve their mental situation. The aim of this study was to investigate the effectiveness of mindfulness-based cognitive therapy on the veterans' spouses with depression, anger, and emotion regulation difficulties. Materials & Methods: In the controlled pretest-posttest semi-experimental study, 60 veterans' spouses were studied in Tehran in 2014. The subjects, selected via purposful sampling, were randomly divded into experimental (n=30) and control (n=30) groups. Data was collected using Spielberger Anger Inventory, Beck Depression Inventory (BDI), and Difficulties in Emotion Regulation Scale (DERS). 10-session mindfulness-based cognitive therapy intervention was done in experimental group. The inventories were completed by the groups in both pretest and posttest stages. Data was analyzed by SPSS 21 software using multivariable covariance analysis. Findings: The mean scores of the overall index of anger expression, depression, and the overall index of the difficulties in emotion regulation in the experimental group were significantly reduced at the posttest stage with the inhibition of the pretest effects, than control group (p<0.001). Conclusion: As a short-term therapy, the mindefulness-based cognitive therapy can simultaneously reduce depression, anger, and the difficulties in emotion regulation in the spouses of the veterans.